The loneliest boy in the world [videorecording (DVD)] - Ashworth, Piers; Harwood, Max; Fiennes-Tiffin, Hero; Ross, Evan; Benson, Ashley, 1989-; Miller, Ben, 1966- (Well Go USA, 2022)
A modern fairytale' with zombies! Oliver lives alone in his late parents' suburban home and faces rejection at every turn. He is tasked with making new friends, and decides his best bet is to build a perfect TV family starting at the local cemetery' where he digs friends up one at a time!